Pengaruh Variabel-Variabel Keuangan pada Initial Return Saham di Pasar Perdana - Aisyah, Isye Siti (Jurnal Trikonomika, 2009)
The aim of this research to examine the financial variables influence in the prospectus through stock initial return in primary market. And also to examine is the firm size as a relationship moderating variable between financial variables (Rate of Return On Total Assets, Total Assets Turn Over, Financial Leverage, Earning Per Share, and Current Ratio) with initial return. There are 48 go public companies in Jakarta Stock Exchange from 2000-2004 aqs the sample for this research. The firm is not a banking company or another financial financial institution and it has a positive return (underpriced). The assessment result with multiple regression can be summarized that generally financial variables influenced initial return, and individually the one that influenced initial return is Financial Leverage, while another variable from Rate of Return On Total Assets, Total Assets Turn Over, Earning Per Share, and Current Ratio have not a significant effect. The research fails to show that firm size as a relationship moderating variable between Rate of Return On Total Assets, Total Assets Turn Over, Financial Leverage, Earning Per Share, and Current Ratio with initial return.